Formulation and characterization of nanolaminated starch based film - Slavutsky, Anibal Marcelo (2014)
Nanolaminated films were formulated by coating a hydrophilic film with a lipid nanolayer. This was performed by coating a starch film with sunflower oil, due to favourable interfacial forces that interact between the oil and the starch film support. The lipid nanolayer presence was corroborated by SEM analyses. Sorption isotherm curves of nanolaminated films show the same trend as starch films used as support but with an important reduction in the film water content through all the aw range studied. The effect on permeability and diffusivity of the driving force (Daw) and aw range, were evaluated. Water diffusion coefficients of oil laminated films are lower than the corresponding to starch films and in both cases, diffusivity decreases with aw. Water vapour permeability depends on the driving force and aw range, and it was concluded that in nanolaminated films, permeation phenomenon is controlled by water diffusion through the hydrophobic nanolayer. Nanolaminated films show an increase in tensile strength and Young module with a decrease in elongation in relation to starch based films.